LEVERS OF CONTROL, CATUR PURUSA ARTHA AND FINANCIAL PERFORMANCE OF VILLAGE CREDIT INSTITUTIONS: BELIEF SYSTEM VERSUS RELIGIOUS VALUES - I Made Pradana Adiputra; Desak Nyoman Sri Werastuti (Jurnal Bisnis dan Akuntansi, 2024)
This research aims to provide empirical evidence about the influence of levers of control (LoC) and their interactions in Catur Purusa Artha on the financial performance of Village Credit Institutions. Using a quantitative approach through a survey (filling out a questionnaire) by 17 Village Credit Institution units via a Google form link, responses were obtained from 51 people consisting of pemucuk, petengen and penirik (non-probability sampling) petengen. Data analysis uses OLS regression and moderated regression analysis (MRA). The research results show that levers of control have a positive effect on the financial performance of Village Credit Institutions. The results of the analysis of the interaction between LoC and the catur purusa artha value have no effect on the financial performance of Village Credit Institutions. The research results show that there is friction between the values of the Catur Purusa Artha organization and the belief system on LoC. The possibility of measuring aspects of organizational values that are indicated to be the cause of the interaction test results cannot be proven in this research. Limitations of the sample and respondents also mean that the research results may not match those expected in the research hypothesis. Evaluation of the use of the Catur Purusa Artha value questionnaire instrument needs to be considered for further research. The implications of research findings show that religious values and belief systems have strength in the implementation of LoC which have an impact on the financial performance of Village Credit Institutions. The role of religious values, namely catur purusa artha, has not been tested much on the effectiveness of LoC.